2008
DOI: 10.1007/s10067-008-0871-7
|View full text |Cite
|
Sign up to set email alerts
|

An increased prevalence of fibromyalgia in iron deficiency anemia and thalassemia minor and associated factors

Abstract: In this study, we evaluated the prevalence of fibromyalgia (FM) in iron deficiency anemia (IDA) and thalassemia minor (TM) patients and associated factors. In addition, we investigated the prevalence of IDA in outpatients with fibromyalgia, and its effect on clinical findings. The study included 205 IDA, 40 TM patients and 100 healthy controls. FM was diagnosed according to 1990 ACR criteria. Whole blood count, biochemical tests, and serum iron parameters were determined. Pain, fatigue, and FM Impact Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
2
21
0
1
Order By: Relevance
“…In an analysis of hair minerals, Kim and colleagues [9] reported significantly lower levels of iron in patients with fibromyalgia compared with healthy age-and BMI-matched controls (P = 0.007). Pamuk and colleagues [10] found an increased prevalence of fibromyalgia in patients with iron-deficiency anemia (P = 0.006) and thalassemia minor (P = 0.025) compared with healthy controls. These studies suggest that iron therapy may have a role in the management of fibromyalgia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In an analysis of hair minerals, Kim and colleagues [9] reported significantly lower levels of iron in patients with fibromyalgia compared with healthy age-and BMI-matched controls (P = 0.007). Pamuk and colleagues [10] found an increased prevalence of fibromyalgia in patients with iron-deficiency anemia (P = 0.006) and thalassemia minor (P = 0.025) compared with healthy controls. These studies suggest that iron therapy may have a role in the management of fibromyalgia.…”
Section: Discussionmentioning
confidence: 97%
“…Kim and colleagues [9] noted that the concentrations of calcium, magnesium, and iron in the hair of women with fibromyalgia were lower than in the hair of control patients, even after adjusting for potential confounders. Pamuk and colleagues [10] demonstrated that the prevalence of fibromyalgia among patients with iron-deficiency anemia and thalassemia minor was higher than among control patients. Finally, Ortancil and colleagues [8] reported that mean serum ferritin levels were lower in patients with fibromyalgia than in control patients.…”
Section: Fibromyalgia Is a Disorder Characterized By Chronic Widesprementioning
confidence: 99%
“…Ferritin levels decrease in the initial stage of iron deficiency, and anemia develops subsequently. In a recent study, the prevalence of FMS was found to be significantly higher in patients with iron deficiency anemia than in healthy controls (Pamuk et al, 2008). They reported that ferritin levels of iron deficiency anemia patients with or without FMS (4.5 ± 2.9 and 3.7 ± 2.2, respectively) did not differ.…”
Section: Discussionmentioning
confidence: 96%
“…Some nonspecific symptoms of IDA and TM, like impaired cognitive function, fatigue or inability to concentrate, may not be explained by only anaemia, and consequently may not respond to therapy. In these cases considering the possibility of a FM diagnosis is recommended, since in this study the results show higher prevalence of FM in IDA and TM patients [59]. A second step will be to understand the role that iron replacement therapy could play in some cases suffering from FM and IDA or TM at the same time.…”
Section: Fibromyalgia and Nutritional Statusmentioning
confidence: 76%